2015
DOI: 10.2298/hemind140917004c
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an RP-HPLC method for quantification of trans-resveratrol in the plant extracts

Abstract: New, simple, cost effective, accurate and reproducible RP-HPLC method was developed and validated for the quantification of trans-resveratrol in the extracts of grape exocarp and seeds. The method has proved to be simpler and faster than available methods. Methanol was used as a mobile phase with a flow rate of 1.0 cm3 min-1, while the quantification was effected at 306 nm. The separation was performed at 35?C using a C18 column. The results showed that the peak area response was linear in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Ethanol mixed with DPPH was used as a control. The method was same as used by Xiao et al (2014), Cvetković et al (2015), Savic et al (2016), and Ilić-Stojanović et al (2017 with slight modification. The formula used for calculation is:…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Ethanol mixed with DPPH was used as a control. The method was same as used by Xiao et al (2014), Cvetković et al (2015), Savic et al (2016), and Ilić-Stojanović et al (2017 with slight modification. The formula used for calculation is:…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In nutraceuticals, the extracts of Fallopia japonica are used as a source of resveratrol. It has been shown that resveratrol exhibits the estrogenic [30], antioxidant [31], antiviral [32], antiplatelet [33], anti-thyroid [34] and cancer chemopreventive activity [35]. Furthermore, resveratrol enhances the expression and activity of endothelial nitric oxide synthase [36] and induces vasorelaxation [37].…”
Section: Resorcinol Derivativesmentioning
confidence: 99%
“…where are A s -absorbance of the samples treated with DPPH radicals, A c -absorbance of the control solution [29].…”
Section: Antioxidant Activitymentioning
confidence: 99%